2009
DOI: 10.1002/pssb.200982272
|View full text |Cite
|
Sign up to set email alerts
|

Role of polymers in CVD growth of nanocrystalline diamond films on foreign substrates

Abstract: Spin coating of PVA polymer with fine grained diamond powder is used as the nucleation treatment for achieving growth of nanocrystalline diamond (NCD) thin films. The growth is realized by standard microwave plasma chemical vapor deposition (CVD). The morphology and character of deposited NCD film is strongly related to the growth temperature. The low temperature process (4308C) results in a growth of well-faceted continuous films. The high temperature process (830 8C) results in voids and openings in the laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In our group, we have developed several procedures for nucleation of diamond films from polymer composites. In these cases, the composite polymer to the substrate was transferred by spin coating of a thin film or by covering the substrate by electrospun nanofibrous textile . In this study, we applied a polyvinyl alcohol (PVA) polymer mixed with fine grained diamond powder.…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have developed several procedures for nucleation of diamond films from polymer composites. In these cases, the composite polymer to the substrate was transferred by spin coating of a thin film or by covering the substrate by electrospun nanofibrous textile . In this study, we applied a polyvinyl alcohol (PVA) polymer mixed with fine grained diamond powder.…”
Section: Introductionmentioning
confidence: 99%
“…9.24(a) ). In addition, we observed that the diamond fi lm surface coverage decreased when a thick polymer fi lm was used as an interlayer (Kromka et al , 2009c). In this case, small openings sized at approximately 200 nm were observed.…”
Section: Seeding Using a Polymer Compositementioning
confidence: 87%
“…(Muller et al , 1998;Daenen et al , 2009;Lu et al , 2012). Similarly, polymer-nanoparticle composites and polyelectrolytenanoparticle bi-layers have recently been developed (Kromka et al , 2009b(Kromka et al , , 2009cScorsone et al , 2009).…”
Section: © Woodhead Publishing Limited 2013mentioning
confidence: 98%
See 1 more Smart Citation
“…[38][39][40][41] In 1 mL of PLGA solution, 0.007 g of the ND powder was added and was homogeneously dispersed by mixing and sonication (Labsonic U-2000, B Braun Biotech, Goettingen, Germany, sonication time 5 seconds). The sonication was performed immediately before electrospinning in order to minimize clustering of diamond nanoparticles.…”
Section: Preparation Of Nanofibrous Membranesmentioning
confidence: 99%